Anti-Reflux Mucosa Ablation in the Treatment of Refractive Gastroesophageal Reflux Disease (Perioperaciina Medicina, 2025)
The article is devoted to antireflux mucosal ablation (ARMA) — a new endoscopic method of treatment of refractory gastroesophageal reflux disease (GERD), unresponsive to standard therapy. ARMA restores cardia function through controlled scarring.The method is indicated for patients with refractory GERD, proton pump inhibitor (PPI) dependence, impaired valve function of the gastroesophageal junction grade II–III according to Hill, and small diaphragmatic hernia (up to 2–3 cm). Contraindications include large hernias, previous gastroesophageal junction surgery, achalasia, severe erosive esophagitis, and Barrett’s esophagus.The procedure includes a diagnostic examination, submucosal injection of saline to create a «cushion» and thermal ablation of the mucosa. Argon plasma ablation, coagulation forceps (e.g. Coagrasper) and a submucosal dissection knife in the Forced Coag mode (effect 2, 40 W) are used for coagulation, creating a white surface without carbonization.Postoperative management involves restriction of physical activity, diet and drug therapy (double dose of PPI). Control endoscopy is performed after 2–3 months.Clinical experience of the «Oberig» clinic (58 patients) showed significant and long-term clinical improvement and improvement of the Hill valve degree in 56 of 58 patients (97%). ARMA is an effective and safe minimally invasive method that requires further study.
Keywords: gastroesophageal reflux disease (GERD); refractory GERD; endoscopic treatment; antireflux mucosal ablation (ARMA); Hill valve